The three levels of leadership how to develop your leadership presence, know how, and skill - Scouller, James (Cirencester Management Books 2000, 2011)
A breakthrough guide to leadership written by an author who has been a CEO and now coaches business leaders. The first leadership guide to focus properly on the psychological keys to leadership success. In all the recent literature on leadership skills and techniques, one element has been consistently missing - the leader's psychology. For the first time, this book sets out a compact, but complete model for successful leadership based on a psychological understanding of the challenges and hidden inner blocks faced by all leaders. Drawing on many years experience first as a CEO himself, and more recently as an executive coach, the author has developed two new groundbreaking models. The first outlines the three levels of leadership. The other explains the human psyche and how to achieve self-mastery. Many people claim that leadership qualities are innate and not learned. This book explodes that myth and shows how all aspiring leaders can rise to the challenge. James Scouller is an accredited coach and partner of The Scouller Partnership, an executive coaching practice in the UK. He was a chief executive of international firms for 11 years before becoming a professional coach in 2004. He holds two postgraduate coaching qualifications and trained in applied psychology at the Institute of Psychosynthesis, London.
Includes bibliographical references (p. 302-308) and index.
Keywords: Leadership --Handbooks, manuals, etc